Analisis Musikal dan Teknik Permainan Biola Minuet Karya Luigi Boccherini - Lanang Riyadi; Yensharti Yensharti (SENDRATASIK UNP, 2022)
This study analyzes the musicological Minuet by Luigi Boccherini which focuses on the analysis of rhythm, melody, form and structure of the work. This research includes qualitative research with a content analysis approach. Data were collected through literature study, observation, labor and documentation. Based on the results of the study, it was found that the minuet by Luigi Boccherini was written in 48 bars, using 3 major strokes starting with 3/4 time signature. The form of the work consists of two macro parts (large) A consists of 4 forming characters, 3 phrases and 14 motifs and B consists of 5 forming characters, 3 phrases and 10 motifs. The work is processed through the formation of motifs with their own characters and developed by literal repetition, ascending sequences, descending sequences and repetitions with variations. In addition, it was found the use of acciaccatura ornamentation in the formation of motif 1 with a combination of the use of syncopation and trill rhythms, shifting the basic notes (modulation) to the a minor scale of part A in character 4. The shifting of basic notes to 2 sharp at the beginning of part B with a characteristic use staccato signs.